A method for in-situ determination of amorphous matter content in aluminum silicate fiber fabrics at high temperature

By adding La2O3 standard samples to aluminum silicate fiber fabrics, using high-temperature in-situ X-ray diffraction technology and custom fitting function, combined with Rietveld full-spectrum fitting method, the accuracy of determining the content of amorphous substances at high temperatures was solved. Accurate amorphous material content determination is achieved, supporting the prediction of the life of fiber fabrics.

CN118817742BActive Publication Date: 2025-02-14TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410834484.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-02-14
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

The existing X-ray diffraction analysis method is difficult to accurately determine the content of amorphous substances at high temperatures in aluminum silicate fiber fabrics, especially when the diffraction peaks of the amorphous phase and the crystalline phase overlap, the traditional Rietveld full-spectrum fitting method cannot be accurately Isolate and fit.

Method used

La2O3 with good crystallinity is used as a standard sample and mixed it with aluminum silicate fiber fabric. The XRD pattern is obtained by high-temperature in situ X-ray diffraction technology, and the amorphous phase and crystalline phase are separated by custom amorphous phase diffraction peak fitting function. The diffraction pattern of the Rietveld full spectrum fitting method is used to accurately calculate the content of amorphous substances.

Benefits of technology

This method can accurately determine the content of amorphous substances at high temperature in aluminum silicate fiber fabrics, eliminate fitting errors, and accurate results, which facilitates data sharing and method standardization, providing important data support for the service life of fiber fabrics at high temperatures. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118817742B_ABST
    Figure CN118817742B_ABST
Patent Text Reader

Abstract

The present invention proposes a method for in-situ determination of the amorphous content of aluminum silicate fiber fabric at high temperature, including adding La2O3 as a standard sample, setting a heating system and obtaining the XRD spectrum of the sample at the target test temperature; performing peak separation processing on the characteristic peaks of the amorphous and crystalline phases in the XRD spectrum, fitting part of the amorphous phase diffraction information separately, and deducting it together with the background information; using the Rietveld method to perform full spectrum fitting on the spectrum deducted from the background, and accurately calculating the content of the amorphous substance. The present invention innovatively adopts the Rietveld full spectrum fitting method to determine the amorphous content of aluminum silicate fiber fabric at high temperature. The characteristic peaks of the amorphous and crystalline phases are separated by data processing software, and the amorphous phase is fitted separately, and then the amorphous phase is deducted together with the background information. Finally, the content of the amorphous substance is accurately calculated by using the Rietveld full spectrum fitting. The method is simple and convenient, easy to operate, and the calculation results are accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of amorphous material content testing, and in particular relates to a method for in-situ measuring the amorphous material content of aluminum silicate fiber fabrics at high temperature. Background Art

[0002] During the service of hypersonic vehicles, the surface temperature of the aircraft rises sharply due to the aerodynamic heating effect, which puts strict requirements on the thermal protection system. Ceramic flexible fiber felt has the advantages of high temperature resistance, low density, thermal shock resistance, and low thermal conductivity. It is currently widely used on the leeward side of reentry vehicles. Ceramic fiber fabric has become an important component of fiber felt because it has the characteristics of high temperature resistance and low thermal conductivity of ceramics and the flexibility of fiber fabrics.

[0003] Aluminum silicate fiber fabric has the advantages of low density, low thermal conductivity, oxidation resistance, corrosion resistance, and excellent thermal shock resistance. It is currently a commonly used fiber fabric on thermal protection fiber felt at 1300℃. However, studies have shown that aluminum silicate fiber fabric is mainly composed of amorphous SiO2 and amorphous Al2O3, which are prone to crystallization in a long-term high-temperature environment (above 1200℃), and form mullite at 1300℃, resulting in internal fiber embrittlement, which ultimately seriously affects the mechanical properties of the fiber fabric, thereby shortening its service life. Therefore, calculating the content of amorphous matter in aluminum silicate fiber fabric during high-temperature service is crucial to establishing the relationship between the content of amorphous matter and the mechanical properties of the fiber fabric, and predicting the service life of the fiber fabric at high temperature.

[0004] At present, the main methods for quantitative analysis of substances include inductively coupled plasma emission spectrometry (ICP), X-ray fluorescence spectrometry (XRF), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction analysis (XRD). The first three methods use element content for quantitative analysis. Since aluminum silicate fiber fabric has the same chemical element composition (Si, Al and O) as the quartz phase precipitated at high temperature and the generated mullite phase, such element-based quantitative analysis methods are not suitable for calculating the content of amorphous substances in aluminum silicate fiber fabric. The theoretical basis of quantitative analysis by X-ray diffraction is that the volume or mass of the substance involved in diffraction is proportional to its diffraction intensity. Compared with other quantitative analysis methods, it has the advantages of relatively short test time, simple operation, high quantitative analysis accuracy, and the ability to analyze multiple phases at the same time. Therefore, X-ray diffraction analysis is currently a more commonly used calculation method for calculating the content of substances.

[0005] At present, the commonly used XRD quantitative analysis methods include external standard method, internal standard method, K value method, etc. The above methods often use the peak intensity of the highest diffraction peak of the phase to replace the integral intensity of the diffraction peak of the phase, so the above methods are all single-peak quantitative analysis methods and can be considered as a semi-quantitative method. Rietveld full spectrum fitting is a technology that fits the entire diffraction spectrum (including overlapping peaks) to obtain rich structural information contained in the XRD spectrum. Different from the traditional single-peak quantitative analysis method that only considers the information of the highest peak of the phase, the Rietveld full spectrum fitting quantitative analysis summarizes all the diffraction peak information of the phase to perform full spectrum analysis and phase composition calculation. Therefore, the accuracy and reliability of its quantitative calculation far exceeds the traditional single-peak method.

[0006] The present invention adopts X-ray diffraction method to obtain the XRD spectrum of the sample to be tested after adding the standard sample, and then uses the Rietveld full spectrum fitting method to obtain the content of amorphous substances. Its main steps are: first, add a standard sample with good crystallinity, resistance to 1300°C, no decomposition in the entire service temperature range, and no peak overlap with the crystalline phase in the sample to be tested in the XRD spectrum. The diffraction spectrum of the sample to be tested (including the standard sample) is collected by XRD, and then the amorphous phase and the background diffraction information in the spectrum are deducted by fitting software, and the relative content of each crystallized substance and the standard sample in the crystalline state is refined and calculated, and finally the content of amorphous substances is converted by the known addition amount of the standard sample. However, studies have shown that when deducting the amorphous phase diffraction information, especially when the amorphous phase and the crystalline phase diffraction peaks overlap in the XRD spectrum, it is difficult to accurately deduct the diffraction information of the amorphous phase by relying on the existing background fitting function, so it is difficult to accurately determine the content of amorphous substances by using the Rietveld full spectrum fitting method.

[0007] In this study, when the heat treatment temperature reaches 1200℃, the aluminum silicate fiber fabric crystallizes and precipitates the cristobalite phase. At this time, in the XRD spectrum, the diffraction peak of the amorphous SiO2 phase and the diffraction peak of the precipitated cristobalite phase overlap significantly at 18-28°. When the heat treatment temperature reaches 1300℃, the amorphous Al2O3 in the aluminum silicate fiber fabric reacts with the generated cristobalite to form mullite, and the mullite and the remaining amorphous SiO2 overlap significantly at 24-32° and 52-68°. Therefore, since the traditional Rietveld full spectrum fitting cannot separate and fit the diffraction spectra of the amorphous phase and the crystalline phase, the quantitative calculation of the amorphous material is ultimately inaccurate.

[0008] To this end, this application is filed. Summary of the invention

[0009] In view of this, the present invention aims to overcome the shortcomings of the above-mentioned problems in the prior art and proposes a method for in-situ determination of the amorphous material content of aluminum silicate fiber fabrics at high temperature.

[0010] In the present invention, La2O3 with good crystallinity is used as a standard sample and mixed evenly with aluminum silicate fiber fabric, and the XRD spectrum of the sample to be tested when it reaches the specified temperature is obtained by high-temperature in-situ X-ray diffraction technology. The peak shape function most suitable for the amorphous phase in the aluminum silicate fiber cloth is optimized in combination with the conventional amorphous phase diffraction peak fitting function, and the diffraction spectrum of the amorphous phase and the crystalline phase is separated and fitted. Subsequently, the amorphous phase diffraction peak and the actual background information are treated as "background" and deducted, and the spectrum deducted from the background is fitted by the Rietveld method. Finally, with the assistance of calibration of the external standard sample (La2O3), the content of each crystalline phase after different heat treatment processes is accurately calculated, and the content of the amorphous substance is finally deduced. The data is objective and true, revealing the crystallization process of aluminum silicate fiber fabric at high temperature, and providing certain data support and theoretical guidance for its product development and engineering application.

[0011] Compared with the standard samples selected for conventional quantitative calculation (such as α-Al2O3, NaCl, CaF2, ZnO, etc.), La2O3 not only has simple chemical properties and symmetrical diffraction peak structure, but more importantly, it does not react with aluminum silicate fiber fabric and cristobalite and mullite generated at high temperature during heat treatment, and does not undergo phase transformation or decomposition below 1300°C. Therefore, the addition of La2O3 will not affect the quantitative analysis process and results.

[0012] Taylor polynomial, Cauchy probability density function, Gaussian distribution function are currently commonly used amorphous phase diffraction peak fitting functions. When the amorphous material content is relatively high, the diffraction peak is independent and the diffraction intensity is relatively high, the above fitting functions can well fit the amorphous phase diffraction peak. However, in the present invention, when the heat treatment temperature is higher than 1200 ° C, the aluminum silicate fiber fabric will undergo crystallization to generate a cristobalite phase. As the temperature continues to rise, amorphous Al2O3 reacts with the generated cristobalite to generate a mullite phase. As the amount of crystallization and the mullite phase increase, the content of amorphous material gradually decreases. This process can be reflected in the X-ray diffraction spectrum as the temperature increases, the diffraction peak intensity of the generated crystalline phase (cristobalite or mullite phase) gradually increases, and the original amorphous phase diffraction intensity gradually weakens. In addition, as the heat treatment temperature increases, the diffraction peaks of the generated crystalline phase and the original amorphous phase overlap to varying degrees. Both of these reasons will make it difficult to use the above fitting function to fit the amorphous phase diffraction peak in the aluminum silicate fiber fabric. Therefore, there is a large error between the calculated amorphous material content and the actual content.

[0013] Studies have shown that the diffraction peaks of amorphous SiO2 and Al2O3 are symmetrical, and this symmetry does not change with the change of content. Combined with the symmetrical characteristics of the amorphous phase peak in aluminum silicate fiber fabrics, the present invention adopts a custom function to fit the amorphous phase diffraction peak on the basis of the conventional amorphous phase diffraction peak fitting function formula model. Compared with the conventional fitting formula, the custom fitting function is closer to the amorphous peak curve and the fitted amorphous peak shape is more symmetrical, so it can achieve accurate fitting of the amorphous phase diffraction peak in aluminum silicate fiber fabrics, and ultimately ensure the accuracy of quantitative calculation of amorphous substances.

[0014] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0015] A method for in-situ determination of amorphous material content in aluminum silicate fiber fabric at high temperature comprises the following steps:

[0016] Step 1: Add La2O3 as a standard sample, set the heating system and obtain the XRD spectrum of the sample at the target test temperature;

[0017] Step 2: Separate the characteristic peaks of the amorphous and crystalline phases in the XRD spectrum, fit part of the amorphous phase diffraction information separately, and deduct it together with the background information;

[0018] Step 3: Use the Rietveld method to fit the entire spectrum after subtracting the background to accurately calculate the content of amorphous substances.

[0019] Furthermore, the step 1 specifically includes the following steps:

[0020] Step 1.1: Select aluminum silicate fiber fabric, grind it thoroughly, and sieve it to obtain the sample to be tested;

[0021] Step 1.2: Add 10%-20% La2O3 powder by mass to the sieved amorphous sample, mix thoroughly and sieve to obtain the sample to be tested;

[0022] Step 1.3: Collect the XRD spectrum of the sample. Use a high-temperature in-situ X-ray diffractometer to increase the temperature according to the heating system. The heating rate is controlled at 5℃ / min-20℃ / min. After the sample is heated to the target temperature, the insulation time is 10s-90min. After the temperature stabilizes, collect the XRD spectrum of the sample.

[0023] Furthermore, the step 2 specifically includes the following steps:

[0024] Step 2.1: Define the diffraction peaks with a half-height width of the diffraction peak greater than 3° in the aluminum silicate fiber fabric as amorphous phase diffraction peaks, use the text data of the XRD spectrum collected in step 1 to call into the fitting software, fit the background curve, export it as "background data", check and mark the 2θ range of the amorphous phase diffraction peaks that are not fitted, especially the 2θ range of the amorphous phase that overlaps with the crystalline phase diffraction peak;

[0025] Step 2.2: Import the text data of the XRD spectrum collected in step 1 into the data processing software, use the custom fitting function to fit the amorphous phase diffraction peaks marked in step 2.1 multiple times, accurately separate the diffraction peaks of the amorphous phase and the crystalline phase, and export the data as "amorphous phase background data";

[0026] Step 2.3: Replace the intensity data in the 2θ range of the amorphous phase diffraction peak marked in the "background data" of step 2.1 with the "amorphous phase background data" refitted in step 2.2 and save it as "new background data".

[0027] Furthermore, the step 3 specifically includes the following steps:

[0028] Step 3.1: Import the text data of the XRD spectrum of the sample to be tested obtained in step 1 and the "new background data" into the refinement software, deduct the "new background data" and perform Rietveld full spectrum fitting to obtain the relative mass fraction of each crystalline phase in the sample to be tested after adding La2O3;

[0029] Step 3.2: According to the actual amount of La2O3 added, the real mass fraction of the crystalline phase in the original sample to be tested is converted to finally obtain the mass fraction of the amorphous material.

[0030] Furthermore, the X-ray diffractometer test conditions used are: using CuK α The light source has a scanning range of not less than 10°-90°, a scanning step of 0.01°, a scanning speed of not more than 2° / min, the 2θ value error of the X-ray diffractometer is within ±0.02°, and the 2θ repeatability is expressed as a standard deviation and shall not exceed 0.002°.

[0031] Furthermore, the instrument parameter file needs to be added when fitting the full spectrum, including the goniometer radius, light source file, and instrument slit width.

[0032] Furthermore, the custom fitting function is as follows:

[0033]

[0034] Where: E A (2θ) is the diffraction intensity; A is the theoretical maximum peak intensity of the glass phase; B is the peak width coefficient; C is the peak center position; and D is other scattering intensities.

[0035] Furthermore, in the step 1.1, the pore size of the sieve used for sieving is 100-200 mesh.

[0036] Furthermore, in the step 1.2, the pore size of the sieve used for sieving is 100-200 mesh.

[0037] Compared with the prior art, the method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature described in the present invention has the following advantages:

[0038] Through in-depth research on the peak structure of the X-ray diffraction spectrum of amorphous materials, the fitting effects of Taylor polynomials, Gaussian functions, Cauchy distribution density probability functions, etc. on amorphous diffraction peaks are systematically analyzed, thereby innovatively establishing the best background curve fitting function. Compared with the traditional fitting function, this fitting function is based on the characteristics of good symmetry of the diffraction peaks of amorphous materials in aluminum silicate fiber fabrics, and uses an iterative convergence method to automatically adjust the coefficients in the fitting formula. The fitting process is not affected by interference factors such as overlapping peaks, and multiple fittings are finally used to ensure that the "background curve function" obtained by fitting is more in line with the peak shape of the amorphous phase itself. On this basis, the present invention uses La2O3 with good crystallinity as a standard sample, obtains the relative content of each crystalline phase in the fiber fabric through full spectrum fitting, and finally converts the content of amorphous phase material by the actual addition amount of La2O3. The present invention innovatively proposes to fit the amorphous phase diffraction peak by modifying the fitting formula, thereby effectively separating the diffraction spectra of the amorphous phase and the crystalline phase. In addition, the present invention uses the Rietveld full spectrum fitting method for the first time to calculate the content of amorphous phase material in aluminum silicate fiber fabrics at high temperature. This method greatly eliminates fitting errors, is simple to operate, produces accurate results, and facilitates data sharing and method standardization, which has a vital impact on predicting the life of fiber fabrics in high-temperature service environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0040] Figure 1 is the phase spectrum of the mixture sample in Example 1;

[0041] Figure 2 The XRD pattern of the mixture sample in Example 1 and the background image of the first fitting;

[0042] Figure 3 The XRD pattern of the mixture sample in Example 1 and the newly fitted background image;

[0043] Figure 4 It is a comparison diagram of the background fitting using different methods in Example 1;

[0044] Figure 5 This is the refined image of the mixture sample in Example 1;

[0045] Figure 6 is the phase spectrum of the sample in Example 2;

[0046] Figure 7 The XRD pattern of the sample in Example 2 and the background image of the first fitting;

[0047] Figure 8 The XRD pattern of the sample in Example 2 and the newly fitted background image;

[0048] Fig. 9 It is a comparison diagram of the background fitting using different methods in Example 2;

[0049] Fig.10 This is a refined image of the sample in Example 2;

[0050] Fig.11 is the phase spectrum of the sample in Example 3;

[0051] Fig.12 The XRD pattern of the sample in Example 3 and the background image of the first fitting;

[0052] Fig.13 The XRD pattern of the sample in Example 3 and the newly fitted background image;

[0053] Fig.14 Comparison diagram of background fitting using different methods in Example 3

[0054] Fig.15 This is a refined image of the sample in Example 3;

[0055] Fig.16 This is the refined image of the mixture sample in Comparative Example 1. DETAILED DESCRIPTION

[0056] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application and are not used to limit the technical solutions of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0057] The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples are all obtained through commercial channels unless otherwise specified. The aluminum silicate fiber fabrics involved in the following examples and comparative examples were purchased from Hubei Feilihua Quartz Glass Co., Ltd. The characterization methods and characterization conditions involved in the following examples and comparative examples are conventional characterization methods and conventional characterization conditions unless otherwise specified.

[0058] Example 1

[0059] Mix amorphous SiO2, cristobalite, La2O3 and mullite in a ratio of 3:2:2:3 and pass through a 150-mesh sieve.

[0060] Collect the XRD spectrum of the mixed sample. Test conditions: using CuK α The light source, scanning step length is 0.01°, scanning speed is 1° / min, and scanning range is 10-100°. Phase analysis is performed on the collected data. The phase analysis results are as follows: Figure 1 shown.

[0061] Import the text data (extension .dat or .txt) of the collected diffraction pattern into data refinement software, such as TOPAS, Jade, GSAS, etc. to fit the background curve, save it as "background data", check the fitted background data and mark the peak position range of the amorphous phase that is not well fitted. Figure 2 As shown, the "background" curve in this XRD spectrum is the background curve automatically fitted by the software. The 2θ range of the amorphous phase diffraction peak is 17°-25°. By zooming in on the amorphous phase curve, it can be found that the background curve fitted within this range does not coincide well with the XRD spectrum curve.

[0062] Import the collected XRD spectrum text data into data processing software, such as Matlab, Python, etc., to extract the amorphous phase text data with a 2θ range of 16.8°-25.2°. Since the amorphous peak and the crystalline peak overlap in this range, the specific 2θ range of the extracted data is: 16.8°-21.2°; 22.3°-25.2°. Through the custom equation Fit the amorphous phase in the spectrum and determine the convergence range: A: the lower limit is 0, no upper limit; B: the lower limit is 0, the upper limit is 1; C: the lower limit is 18, the upper limit is 24; D: the lower limit is 0, no upper limit. The fitting formula after the software automatically iterates and converges is: Goodness of fit R 2 The value is 0.987, indicating that the fitting effect is very good. The intensity data in the range of 16.8°-25.2° after fitting are exported and replaced with the 2θ and intensity values ​​in the corresponding range in the background data, and saved as new background data. Figure 3is the XRD pattern of the mixture sample and the new fitting background image, Figure 4 From the comparison diagram of the background fitted using different methods, it can be found that the new background has a higher degree of overlap with the XRD diffraction peak, and the fitted amorphous peak is more symmetrical.

[0063] The new background data was used to remove the background, and the full spectrum was refined. The fitting spectrum was as follows Figure 5 As shown. The refined Rwp is 9.16%, indicating that the refined data is good. The relative contents of cristobalite, La2O3, and mullite are 28.9%, 28.4%, and 42.7%, respectively. The content of amorphous SiO2 is 29.58% after conversion based on the La2O3 content of 20%. The result is not much different from the result of the configuration, and the error between the two is only 1.4%.

[0064] Example 2

[0065] The aluminum silicate fiber fabric was cut into pieces and ground, and passed through a 200-mesh sieve to obtain aluminum silicate fiber fabric powder. The sieved aluminum silicate fiber fabric powder was mixed with high-crystallinity La2O3 powder in a mass ratio of 4:1, ball-milled, and passed through a 200-mesh sieve to obtain a uniformly mixed sample to be tested.

[0066] Using high temperature in-situ X-ray diffraction technology, the temperature was raised at 5°C / min. After the sample was heated to 1200°C, it was kept warm for 75 minutes. After the temperature stabilized, the XRD spectrum of the sample was collected. The test conditions are: CuK α The light source, scanning step length is 0.01°, scanning speed is 1° / min, and scanning range is 10-100°. The collected data is analyzed for phase. The results of phase analysis are as follows: Figure 6 As shown, the crystalline phase in the aluminum silicate fiber fabric includes not only La2O3 but also cristobalite phase.

[0067] Import the text data of the collected diffraction spectrum into data refinement software, such as TOPAS, Jade, GSAS and other software to fit the background curve, save it as background data, check the fitted background data and mark the peak position of the amorphous phase that is not well fitted. Figure 7 As shown in the figure, the "background" curve in this XRD spectrum is the background curve automatically fitted by the software, and the 2θ range of the amorphous phase diffraction peak is 17.3°-24°; 30°-33°; 34°-42°; 43°-48°; 58°-63°; 64°-70°. Zooming in on the amorphous phase curve, it can be found that the background curve fitted in the four 2θ ranges of 17.3°-24°; 34°-42°; 43°-48°; 64°-70° does not coincide well with the XRD spectrum curve.

[0068] Import the text data of the collected diffraction patterns into data processing software, such as Matlab, python and other software, and extract the amorphous phase text data in the four ranges of 2θ: 17.3°-24°; 34°-42°; 43°-48°; 64°-70°. There are overlapping peaks in 17.3°-24°; 34°-42°; 43°-48°, so the 2θ interval of the text data extracted from 17.3°-24° is 17.3°-20.74° and 22.1°-24°; the 2θ interval of the text data extracted from 34°-42° is 34.5°-38.7° and 40.5°-42°; the 2θ interval of the text data extracted from 43°-48° is 43.5°-45.6° and 46.4°-48°; the range of other amorphous phase text data remains unchanged. Use custom equations respectively Fit the amorphous phase in the spectrum. The convergence range is shown in Table 1. The text data of the three amorphous phase diffraction peaks are automatically iterated and converged by the data processing software. The converged formulas are:

[0069]

[0070] Goodness of fit R 2 The values ​​are 0.962, 0.971, 0.982 and 0.972, indicating that the fitting effect is very good. The intensity data in the range of 17.3°-24°, 34°-42°, 43°-48° and 64°-70° after fitting are exported and replaced with the 2θ and intensity values ​​in the corresponding range in the background data, and saved as new background data. Figure 8 is the XRD pattern of the mixture sample and the new fitting background image, Fig. 9 From the comparison diagram of the background fitted using different methods, it can be found that the new background has a higher degree of overlap with the XRD amorphous phase, and the fitted amorphous peak is more symmetrical.

[0071] Table 1

[0072]

[0073]

[0074] Select the new background data to subtract the background and perform full spectrum fitting. The fitting spectrum is as follows Fig.10 The fitting Rwp is 8.33%, indicating that the refined data is good. The relative contents of cristobalite and La2O3 are 23.3% and 76.7% respectively. The amorphous material content is 73.9% after conversion based on the La2O3 content of 20%.

[0075] Example 3

[0076] The aluminum silicate fiber fabric was cut into pieces and ground, and passed through a 200-mesh sieve to obtain aluminum silicate fiber fabric powder. The sieved aluminum silicate fiber fabric powder was mixed with high-crystallinity La2O3 powder in a mass ratio of 17:3, ball-milled, and passed through a 200-mesh sieve to obtain a uniformly mixed sample to be tested.

[0077] Using high temperature in-situ X-ray diffraction technology, the temperature was raised at 5°C / min. After the sample was heated to 1300°C, it was kept warm for 15 minutes. After the temperature stabilized, the XRD spectrum of the sample was collected. The test conditions are: CuK α The light source, scanning step length is 0.01°, scanning speed is 1° / min, and scanning range is 10°-90°. Phase analysis is performed on the collected data. The phase analysis results are as follows: Fig.11 As shown, the crystalline phase in the aluminum silicate fiber fabric includes not only La2O3 but also mullite phase.

[0078] Import the text data of the collected diffraction spectrum into data refinement software, such as TOPAS, Jade, GSAS, etc., to fit the background curve and save it as background data. Check the fitted background data and mark the peak position of the amorphous phase that is not well fitted. Fig.12 As shown in the figure, the "background" curve in this XRD spectrum is the background curve automatically fitted by the software, in which the 2θ range of the amorphous phase diffraction peak is 21°-32° and 51°-68.8°. Zooming in on the amorphous phase curve, it can be found that the background curve fitted in these two amorphous ranges has poor coincidence with the XRD spectrum curve.

[0079] Import the text data of the collected diffraction patterns into data processing software, such as Matlab, python, etc., and extract the text data of the amorphous phase in the 2θ range of 21°-32° and 51°-68.8°. Since the above amorphous peaks overlap with the crystalline peaks, the specific 2θ range of the extracted data of 21°-32° is:

[0080] 21°-24.5°, 26.6°-27°, 28.1°-28.5°, 31.3°-32°;

[0081] The 2θ range of the specific extracted data from 51°-68.8° is:

[0082] 51°-51.6°, 52.7°-53°, 56.5°-56.9°, 58.2°-59.5°, 67.8°-68.8°. Respectively through custom equations The amorphous phase in the fitting spectrum is determined to have a convergence range as shown in Table 2. The text data of the two amorphous phase diffraction peaks are automatically iterated and converged by the data processing software. The converged formulas are:

[0083]

[0084] Goodness of fit R 2 The values ​​are 0.992 and 0.964, indicating that the fitting effect is very good. The intensity data in the range of 21°-32° and 51°-68.8° after fitting are exported and replaced with the 2θ and intensity values ​​in the corresponding range in the background data, and saved as new background data. Fig.13 is the XRD pattern of the mixture sample and the new fitted background image. Fig.14 From the comparison diagram of the background fitted using different methods, it can be found that the new background has a higher degree of overlap with the XRD amorphous phase, and the fitted amorphous peak is more symmetrical.

[0085] Table 2.

[0086]

[0087]

[0088] Select the new background data to subtract the background and perform full spectrum fitting. The fitting spectrum is as follows Fig.15 The fitting Rwp is 7.48%, indicating that the refined data is good. The relative contents of mullite and La2O3 are 77.75% and 22.25% respectively. The amorphous material content is 32.6% after conversion based on the La2O3 content of 15%.

[0089] Comparative Example 1

[0090] Compared with Example 1, the collected diffraction pattern does not fit the amorphous diffraction information separately, and the rest is the same as Example 1.

[0091] Fitting spectrum Fig.16 As shown, the fitting Rwp is 16.8%, indicating that the quality of the refined data is poor. The relative contents of cristobalite, La2O3, and mullite are 28.6%, 27.3%, and 44.1%, respectively. After conversion based on the La2O3 content of 20%, the content of amorphous material is 26.7%. The results are quite different from the results of the configuration, with an error of 11%.

[0092] By comparing Comparative Example 1 with Example 1, it can be seen that using data processing software to fit the diffraction information of the amorphous cell alone can greatly optimize the background subtraction during the refinement process, improve the accuracy of the refined data, and reduce the error of the amorphous material content.

[0093] In summary: The present invention innovatively adopts the Rietveld full spectrum fitting method to determine the amorphous content of aluminum silicate fiber fabrics at high temperatures. The characteristic peaks of the amorphous and crystalline phases are separated by data processing software, and the amorphous phase is fitted separately, and then the amorphous phase is deducted together with the background information. Finally, the Rietveld full spectrum fitting is used to accurately calculate the content of amorphous material. This method is simple, convenient, easy to operate, and the calculation results are accurate. In addition to being applicable to the content of amorphous material in the service process of the thermal protection system of the test aircraft of the present invention, it can also be promoted to other related fields of accurate testing of amorphous material content.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature, characterized in that: The steps include: Step 1: Add La2O3 as a standard sample, set the heating system and obtain the XRD spectrum of the sample at the target test temperature; Step 2: Separate the characteristic peaks of the amorphous and crystalline phases in the XRD spectrum, fit part of the amorphous phase diffraction information separately, and deduct it together with the background information; Step 2.1: Define the diffraction peaks with a half-height width of the diffraction peak greater than 3° in the aluminum silicate fiber fabric as amorphous phase diffraction peaks, use the text data of the XRD spectrum collected in step 1 to import into the fitting software, fit the background curve, export it as "background data", check and mark the 2θ range of the amorphous phase diffraction peaks that are not fitted well and the 2θ range of the amorphous phase that overlaps with the crystalline phase diffraction peaks; Step 2.2: Import the text data of the XRD spectrum collected in step 1 into the data processing software, use the custom fitting function to fit the amorphous phase diffraction peaks marked in step 2.1 multiple times, accurately separate the diffraction peaks of the amorphous phase and the crystalline phase, and export the data as "amorphous phase background data"; the custom fitting function is as follows: Where: E A (2θ) is the diffraction intensity; A is the maximum peak intensity of the theoretical glass phase; B is the peak width coefficient; C is the peak center position; D is the other scattering intensity; Step 2.3: Replace the intensity data of the 2θ range of the amorphous phase diffraction peak marked in the "background data" of step 2.1 with the "amorphous phase background data" refitted in step 2.2 and save it as "new background data"; Step 3: Use the Rietveld method to fit the entire spectrum after subtracting the background to accurately calculate the content of amorphous substances.

2. The method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature according to claim 1, characterized in that: The step 1 specifically includes the following steps: Step 1.1: Select aluminum silicate fiber fabric, grind it thoroughly, and sieve it to obtain the sample to be tested; Step 1.2: Add 10%-20% La2O3 powder by mass to the sieved amorphous sample, mix thoroughly and sieve to obtain the sample to be tested; Step 1.3: Collect the XRD spectrum of the sample. Use a high-temperature in-situ X-ray diffractometer to increase the temperature according to the heating system. The heating rate is controlled at 5℃ / min-20℃ / min. After the sample is heated to the target temperature, the insulation time is 10s-90min. After the temperature stabilizes, collect the XRD spectrum of the sample.

3. The method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature according to claim 1, characterized in that: The step 3 specifically includes the following steps: Step 3.1: Import the text data of the XRD spectrum of the sample to be tested obtained in step 1 and the "new background data" obtained in step 2.3 into the refinement software, deduct the "new background data" and perform Rietveld full spectrum fitting to obtain the relative mass fraction of each crystalline phase in the sample to be tested after adding La2O3; Step 3.2: According to the actual amount of La2O3 added, the real mass fraction of the crystalline phase in the original sample to be tested is converted to finally obtain the mass fraction of the amorphous material.

4. The method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature according to claim 2, characterized in that: The X-ray diffractometer test conditions used were: CuK α light source, a scanning range of not less than 10°-90°, a scanning step of 0.01°, a scanning speed of not more than 2° / min, and a 2θ value error of the X-ray diffractometer within Within ±0.02°, 2θ repeatability is expressed as standard deviation and shall not exceed 0.002°.

5. The method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature according to claim 1, characterized in that: When fitting the full spectrum, the instrument parameter file needs to be added, including the goniometer radius, light source file, and instrument slit width.

6. The method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature according to claim 2, characterized in that: In the step 1.1, the pore size of the sieve used for sieving is 100-200 meshes.

7. The method for in-situ determination of amorphous matter content in aluminum silicate fiber fabric at high temperature according to claim 2, characterized in that: In the step 1.2, the pore size of the sieve used for sieving is 100-200 meshes.

Citation Information

Patent Citations

  • Crystalline-state-containing trace material evidence quantitative characterization method

    CN117030763A